Understanding why immigrant children underperform: evidence from Italian compulsory education. Issue 10 (27th July 2022) - Triventi, Moris; Vlach, Eleonora; Pini, Elisa
ABSTRACT: We aim to investigate the extent to which children of immigrants achieve lower levels of academic proficiency in reading and mathematics compared to native students in compulsory education in Italy. Advancing the current literature, we investigate in a more comprehensive way the importance of a variety of individual characteristics in accounting for children of immigrants' penalties. In particular, we examine the role of family structure, parents' socio-economic resources, parents' cultural and educational resources and students' school-related attitudes and behaviour. The empirical analysis makes use of a unique dataset collected by the National Institute for the Evaluation of the Italian School System (INVALSI) on the whole population of students enrolled in primary school (5th grade) and lower secondary education (6th grade) in 2012. We apply Kitagawa-Blinder–Oaxaca decomposition models to identify the net contribution of each characteristic to the disadvantages faced by immigrant offspring. We found partial support for the composition hypothesis (socio-economic resources) and culturalist explanations (especially language spoken at home), but pupils' school-related attitudes – which received less attention in the previous literature – also contribute to explaining the gaps, especially in lower secondary school.